Beneath the surface: imaging techniques and the Jericho Skull - Fletcher,A; Pearson,J; Molleson,T; Abel,R; Ambers,J; Wiles,CC (British Museum Publications Limited, 2014)
A key publication on the British Museum's approach to the ethical issues surrounding the inclusion of human remains in museum collections and possible solutions to the dilemmas relating to their curation, storage, access management and ...